The study of physical and chemical properties of Thai distilled spirits. - สายสิทธิ์, ประเสริฐ; สุคนธ์รักษ์, เมทนี (Agriculture and Natural Resources, 1980)
A total of 19 liquor samples comprised of 11 Thai liquors and three well known foreign liquors were analysed for 15 physical and chemical properties. Thai liquors were arranged into four groups according to processing methods and each group was analysed in comparison with the similar foreign brands as follows : 1. Grain Spirit [e.g. Lao Khao]. Compared with Tequila. 2. Chinese Whiskey [e.g. Chiang Shun]. No. comparison. 3. Special Blended Whiskey [e.g. Mae Khong, Raet Thong and Kai Daeng]. Compared with White Label Scotch Whiskey. The results of this investigation indicated that Lao Khao was inferior to acids and esters seemed to decrease as the ethyl alcohol content increased. Fusel oils were very high in one of the samples and in the sample also contained exceptionally high amount of copper. Chiang Shun whiskey had very similar results as Jamaica dark rum as far as chemical and physical properties were concerned. However, organoleptic tests would immediately separate them out. Special blended whiskey when compared with Jamaica dark rum was lighter in color and lesser in esters, aldchydes and fusel oils contents. Imitation scotch wiskey was superior to White Label scotch whiskey only lesser in fusel oils and methyl alcohol contents. Other properties, such as volatile acids, esters and aldehyde contents were inferior to the White Label.